Analisis Pengawasan dan Kedisiplinan Terhadap Kinerja Karyawan Indo Suhar Jaya (Narma Toserba Narogong) - Elsa Rahmawati; Rini Wijayanti (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the effect of supervision and discipline on the performance of employees of PT. Indo Suhar Jaya (Narma Narogong Department Store). This study used descriptive qualitative method. The techniques used in collecting data in this study included observation, interviews and direct documentation of PT. Indo Suhar Jaya (Narma Narogong Department Store). The results of the study show that supervision and discipline in this study do not have a significant effect on employee performance. Based on the results of observations and interviews with 15 informants, supervision and discipline have been carried out well, however, employee performance is still very low, seen from the average attendance rate per month, which only reaches 66%. Keywords: Supervision, Discipline, Performance